Interval Oscillation Criteria for Nonlinear Neutral Impulsive Differential Equations (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we study the interval oscillation for nonlinear neutralimpulsive differential equations. Sufficient condition for the interval oscillationof the equations is obtained by using Riccati transformation and estimatingthe ratio of unknown functions $y(t − σ(t))$ and $y(t).$ Some known results aregeneralized and improved. An example is given to illustrate the results.